Nuclear Factor-kappaB in Autoimmunity: Man and Mouse - Miraghazadeh, Bahar; Cook, Matthew C. (Frontiers in Immunology, 2018)
NF- B (nuclear factor-kappa B) is a transcription complex crucial for host defence mediated by innate and adaptive immunity, where canonical NF- B signalling, mediated by nuclear translocation of RelA, c-Rel and p50, is important for immune cell activation, differentiation and survival. Non-canonical signalling mediated by nuclear translocation of p52 and RelB contributes to lymphocyte maturation and survival, and is also crucial for lymphoid organogenesis. We outline NF- B signalling and regulation, then summarise important molecular contributions of NF- B to mechanisms of self-tolerance. We relate these mechanisms to autoimmune phenotypes described in what is now a substantial catalogue of immune defects conferred by mutations in NF- B pathways in mouse models. Finally, we describe Mendelian autoimmune syndromes arising from human NF- B mutations, and speculate on implications for understanding sporadic autoimmune disease.